Application of silver diamine fluoride in dentistry: A review - Mahsa Mansouri (Journal of Dental Medicine, 2013)
U ntreated caries are common findings in low-income communities. Treatment of dental caries in young children is challenging and requires a high skill and high cost of dental anesthesia for control ling patients and thus, chemical methods for arresting dental caries have been proposed. Silver Diamine Fluoride (SDF) is a material that is used to control and to arrest dental caries , especially in primary teeth . It is noninvasive, safe , easy to use , and cost-effective. The SDF can be used as a therapeutic agent in oral health projects in low-income communities . In this article we review ed the silver diamine fluoride and its application in dentistry.